From reactive to proactive banking : connecting with customers with context-aware mobile technology - Veikkolainen, Tinja (My University, 2013)
Mobile technology has been employed in banking for already two decades. However, its significance this far has been modest. It is expected that the industry will change a lot in the future. Elements of this change include tightening of competition, considering customer’s individual and changing needs, becoming involved in customer’s life and being where customers are. The goal of this study is to explore these fields with regard to Finnish banking as well as investigate selected consumers’ views towards this kind of new service approach. It can be divided into three questions: • What kinds of mobile services does the Finnish banking industry currently offer for consumers and what expectations do experts and consumers have towards them? o What is consumers’ attitude towards a context-aware service approach in the banking industry and what are the suggested tools for it? o What factors define clients’ adoption intentions towards the new context-aware service approach? Which factors do they consider most important? In order to create the framework for the study, both Finnish and foreign scientific and professional literature considering evolution of the industry and innovation adoption has been used. The empirical part of the study consists of 11 interviews, including 6 expert interviews and 5 consumer interviews. The results show that the selected consumers reacted very positively to the suggested new service approach that considers them as a person and aims at simplifying their banking. The consumers appreciated especially solutions that simplified their everyday banking. Also proactive actions from a bank was considered important especially in everyday banking, as long as the customer was able to define the amount and way of contacts he received. According to the findings banks should aim at supporting their customers more than they do now. However, they also need to pay attention to not irritate their customers by excessive contacts. Banks should also open-mindedly introduce new technologies to their customers. Key words